1984
DOI: 10.1366/0003702844555115
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Characterization of Different Water Types inside Reverse Micelles

Abstract: The three Gaussian components of the IR stretching band of OH for reverse micelles of egg yolk L-α-phosphatidylcholine in benzene have been characterized in frequency, bandwidth, and extinction coefficient. The different types of water identified inside the micelles correspond to hydration layers around the phospholipid polar heads, the first containing up to ∼11 water molecules per polar head, the second with a maximum of 10–12 water molecules per polar head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Typical ν 1,3 (OH) bands of gradually hydrated DODPC are displayed in Figure . The band shapes obtained in the L α and gel states are very similar and resemble the typical structure of the ν 1,3 (OH) band of fully or partially hydrated PC lipids in the fluid state. The broad feature consists of subbands assigned to the symmetric and antisymmetric stretching vibration of free, i.e., non-hydrogen-bound, OH groups (3615 cm -1 ) and of hydrogen-bound OH-groups (<3615 cm -1 ) and to the Fermi resonance (3280 cm -1 ) at 2ν 2 (OH), where ν 2 (OH) ≈ 1650 cm -1 is the H 2 O bending vibration . In general, the ν 1,3 (OH) bandwidth reflects the distribution of hydrogen bonds of variable strength among a variety of binding sites.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Typical ν 1,3 (OH) bands of gradually hydrated DODPC are displayed in Figure . The band shapes obtained in the L α and gel states are very similar and resemble the typical structure of the ν 1,3 (OH) band of fully or partially hydrated PC lipids in the fluid state. The broad feature consists of subbands assigned to the symmetric and antisymmetric stretching vibration of free, i.e., non-hydrogen-bound, OH groups (3615 cm -1 ) and of hydrogen-bound OH-groups (<3615 cm -1 ) and to the Fermi resonance (3280 cm -1 ) at 2ν 2 (OH), where ν 2 (OH) ≈ 1650 cm -1 is the H 2 O bending vibration . In general, the ν 1,3 (OH) bandwidth reflects the distribution of hydrogen bonds of variable strength among a variety of binding sites.…”
Section: Resultssupporting
confidence: 53%
“…parts a and c of Figure ). It represents an approximate measure of the amount of water bound to the lipid 31,46,47 regardless of slight variations of the extinction coefficients of the water fractions differing in their H-bond characteristics 6 Number of water molecules per lipid, R WL (a), wavenumbers at half-maximum absorbance (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Further hydration, even past the percolation threshold, results in the aqueous environment becoming progressively more bulklike in nature. While there is evidence for the existence of three water types in the spherical nonorganogel forming lecithin/benzene reverse micelles, studies of lecithin/cyclohexane reverse micelles detect only two types, strongly bound and free. In contrast, by accounting for solvated monomers, Maitra et al find that for micelles between w 0 = 4.8 to 6.8, the hydration range we have studied, half the water population is bound and the other half free.…”
Section: Discussionmentioning
confidence: 99%
“…The first water type is considered to be strongly bound to the surfactant headgroup, while the final type is considered to be bulklike. Although results vary, several studies have found the existence of three water types in various reverse micellar systems. , …”
Section: Introductionmentioning
confidence: 99%
“…Water molecules in bulk state form hydrogen bonds in tetrahedral arrangements that are constantly breaking and forming, and this dynamical structure can be disrupted when it is confined in small cavities , or at interfaces. , The properties of highly structured water are different from those of water in the bulk. In reverse aggregates of surfactants, water may be found as bound water and/or as free water. , Primary bound water is interacting directly with the polar heads of the surfactants and forms the first hydration shell; secondary bound water is next to primary hydration shell and is bound less tightly; free water is present in stabilized water pools and resembles bulk water, although the dynamics of the entrapped water in the aggregates may be slower. The nature of the hydrophilic segments also affects the polarity of entrapped water.…”
Section: Introductionmentioning
confidence: 99%